Swelling capacity and degradation behaviour of poly(lactic-co-glycolic acid) tissue engineering scaffold through atelocollagen, fibrin or, combination of atelocollagen and fibrin addition - Mohamad, Mohd Yusof; Mohamed Amin, Muhammad Azri Ifwat; Md Nazir, Noorhidayah; Ahmad Radzi, Muhammad Aa’zamuddin; Hashim, Rosyafirah; Zulkifly, Ahmad Hafiz; Sha'ban, Munirah (UTM, 2016)
Swelling capacity and degradation behaviour are important factors for biomaterial scaffold in tissue engineering (TE). Poly(lactic-co-glycolic acid) (PLGA) is a synthetic polymer used commonly as scaffolding material. Major concern with PLGA use is the trigger of inflammatory reaction damaging cells in vivo. Incorporation of natural polymers i.e. atelocollagen and/or fibrin onto PLGA may compensate those effects. This present study aimed to evaluate the swelling capacity and degradation behaviour of PLGA when added with atelocollagen, fibrin or, combination of both atelocollagen and fibrin. Atelocollagen type II has no telopeptide region and forms gel like structure at body temperature. Plasma-derived fibrin is reported to reduce inflammation caused by PLGA. Combination of both atelocollagen and fibrin could enhance PLGA properties. Porous PLGA scaffolds were fabricated via solvent-casting/salt-leaching method using salt as porogen. Atelocollagen was then added and cross-linked with the PLGA using 1-Ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-Hydroxysuccinimide (NHS) to form PLGA/atelocollagen (PA) scaffold. Plasma-derived fibrin was added to the PLGA and the prefabricated PLGA/atelocollagen scaffold to form PLGA/fibrin (PF) and PLGA/atelocollagen/fibrin scaffold (PAF) respectively. Calcium chloride was used to polymerize plasma-derived fibrin onto those scaffolds. Swelling test was performed by immersing the scaffolds in water for 24-hour. Hydrolytic degradation was performed by immersing the scaffolds in simulated body fluid (SBF) and the percentage of reduction was recorded at 28 days. Four scaffolds groups i.e. (1) PLGA alone, (2) PLGA/atelocollagen [PA], (3) PLGA/fibrin [PF], and (4) PLGA/atelocollagen/fibrin [PAF] were compared in this study. The swelling ratio of PA scaffold group (192.57±41.96%) had significantly increased compared to other groups (PLGA= 40.19±4.89%; PF=52.00±23.48%; PAF=66.59±13.38%). In terms of degradation, PA group exhibited significant weight loss (497.11±76.65%) over other groups after 28 days in SBF. These findings suggest PLGA/atelocollagen without fibrin is sufficient to increase swelling capacity and offer higher degradation properties.